Perceived effort of funtional activities after a period of mechanical ventilation - R. Roos; H. van Aswegen; C. J. Eales (AOSIS, 2002)
A case report to assess exercise testing post-mechanical ventilation, using functional activities while monitoring changes in the physiological parameters and subjective rating of perceived exertion.  The case report subject was able to use the Modified Borg Scale to report  her perception of perceived exertion during functional exercise testing.  An increase in heart rate, respiratory rate and Modified Borg Scale rating was noted on progression through the exercise test.  Difficulty was experienced with subject follow-up due to discharged from hospital as soon as the patient was considered to be medically stable.  The subject was unable to complete the functional exercise test before discharge.